2022
DOI: 10.1038/s41467-022-31221-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustained electricity generator driven by the compatible integration of ambient moisture adsorption and evaporation

Abstract: Generating sustainable electricity from ambient humidity and natural evaporation has attracted tremendous interest recently as it requires no extra mechanical energy input and is deployable across all weather and geography conditions. Here, we present a device prototype for enhanced power generation from ambient humidity. This prototype uses both heterogenous materials assembled from a LiCl-loaded cellulon paper to facilitate moisture adsorption and a carbon-black-loaded cellulon paper to promote water evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 40 publications
0
113
1
Order By: Relevance
“…In general, the electrical output originates from the ow potential. 40,41 When water passes through the charged and narrow nanochannel, EDL overlapping effects make counterions pass and form a ow potential. The length of EDL overlapping is equal to the Debye length (k D −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the electrical output originates from the ow potential. 40,41 When water passes through the charged and narrow nanochannel, EDL overlapping effects make counterions pass and form a ow potential. The length of EDL overlapping is equal to the Debye length (k D −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our best knowledge, this current level is the highest continuous current that can be generated by a single HG device (Figure 5e). [7,8,11,18,[43][44][45][46][47][48][49][50] Figure 5b shows the V oc of 0.81 V for more than 8 h, which demonstrates the long-time durability of SiNWs-based HG. The V oc can reach ≈1.6, ≈2.4, and ≈3.2 V when two, three, and four single units are in-serial connected (Figure 5d).…”
Section: Potential Application Of Sinws-based Hg/ssgmentioning
confidence: 93%
“…1−5 The preferential electrokinetic interaction in a MEG occurs during directional moisture evaporation, which spatially dissociates the attractive charges on the surface from the unbound counter-charges, thereby giving rise to the characteristic built-in charge potential. 6,7 As a pioneering work, Ghosh et al observed an output voltage between two electrodes placed on carbon nanotubes when water flowed through the nanotube network. 8 Numerous efforts have been made to further facilitate the preferential charge separation in a MEG by developing materials with various surface functional groups, 9,10 high surface area, 11 and high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the preferential interaction of ions from either moisture or water with various hydrophilic materials, as well as the ion-selective functional groups exposed to the surface on such materials, moisture-driven energy generators (MEGs) are a promising technology for next-generation energy conversion. The preferential electrokinetic interaction in a MEG occurs during directional moisture evaporation, which spatially dissociates the attractive charges on the surface from the unbound counter-charges, thereby giving rise to the characteristic built-in charge potential. , As a pioneering work, Ghosh et al observed an output voltage between two electrodes placed on carbon nanotubes when water flowed through the nanotube network . Numerous efforts have been made to further facilitate the preferential charge separation in a MEG by developing materials with various surface functional groups, , high surface area, and high conductivity .…”
Section: Introductionmentioning
confidence: 99%